Human Resource Information System implementation readiness in the Ethiopian health sector: a cross-sectional study - Eyilachew Dilu; Measho Gebreslassie; Mihiretu Kebede (BMC, 2017)
Abstract Background Health workforce information systems in low-income countries tend to be defective with poor relationship to information sources. Human Resource Information System (HRIS) is currently in a pilot implementation phase in the Federal Ministry of Health and Regional Health Bureaus of Ethiopia. Before scaling up the implementation, it is important to understand the implementation readiness of hospitals and health departments. The aims of this study were to assess the readiness for HRIS implementation, identify associated factors, and explore the implementation challenges in public hospitals and health departments of the Amhara National Regional State, Ethiopia. Methods An institution-based cross-sectional study supplemented with a qualitative study was conducted from the 15th of February to the 30th of March 2016 in 19 public hospitals and health departments of the Amhara National Regional State, Ethiopia. A self-administered questionnaire was used to collect the data. The questionnaire includes items on socio-demographic characteristics and questions measuring technical, personal, and organizational factors adapted from the 32-item questionnaire of the Management Science for Health (MSH) HRIS readiness assessment tool. The data were entered and analyzed with statistical software. Descriptive statistics and bivariate and multivariable logistic regression analyses were performed. Odds ratios with 95% confidence interval were computed to identify the factors statistically associated with readiness of HRIS implementation. In-depth interviews and observation checklists were used to collect qualitative data. Thematic content analysis was used to analyze the qualitative data. Result A total of 246 human resource (HR) employees and 16 key informants have been included in the study. The HR employee's level of readiness for HRIS implementation in this study was 35.8%. Employee's Internet access (AOR = 2.59, 95%CI = 1.19, 5.62), availability of separate HR section (AOR = 8.08, 95%CI = 3.69, 17.70), basic computer skills (AOR = 6.74, 95%CI = 2.75, 16.56), and fear of unemployment (AOR = 2.83, 95%CI = 1.27, 6.32) were associated with readiness of HRIS implementation. Poor logistic supply, lack of competency, poor commitment, and shortage of finance were the challenges of HRIS implementation. Conclusion In this study, readiness of HRIS implementation was low. Strategies targeting to improve skills, awareness, and attitude of HR employees would facilitate the implementation process.